2011
DOI: 10.1007/s11631-011-0529-z
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical, REE-geochemical and fluid inclusion studies on some uranium occurrences, Gabal Gattar, Northeastern Desert, Egypt

Abstract: Altered granite occurrences (GII and GV) at Gabal (G.) Gattar are the most important mineralized rocks hosting U-mineralization in Egypt. This mineralized granite is affected by multi-stage hydrothermal alteration processes along brittle structures. This alteration comprises pre-ore alkali-metasomatism and ore-stage hydrothermal hematitization, silicification, kaolinitization, fluoritization, carbonatization and episyenitization. Autoradiographic examination indicates that primary uranium mineralization is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 37 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The mean U and Th levels of the examined pegmatites are considerably enriched in both U and Th mean levels 1700.91 ppm and 2881.86 ppm, respectively, as compared to the ranges and averages of Reference [38], (1-6 ppm U and 1-23 ppm Th) [39] and (3 ppm U and 8-17 ppm Th) [40]. eTh/eU ratios in igneous rocks are 3 or 4:1 [41]; however, eTh/eU ratios of the studied mineralized pegmatites have average ratios of 1.7, which is lower than the average of igneous rocks, suggesting uranium enrichment. Some radioelements' inter-relationships could clarify the geochemistry of uranium and thorium.…”
Section: Radioelement Distributionmentioning
confidence: 80%
See 1 more Smart Citation
“…The mean U and Th levels of the examined pegmatites are considerably enriched in both U and Th mean levels 1700.91 ppm and 2881.86 ppm, respectively, as compared to the ranges and averages of Reference [38], (1-6 ppm U and 1-23 ppm Th) [39] and (3 ppm U and 8-17 ppm Th) [40]. eTh/eU ratios in igneous rocks are 3 or 4:1 [41]; however, eTh/eU ratios of the studied mineralized pegmatites have average ratios of 1.7, which is lower than the average of igneous rocks, suggesting uranium enrichment. Some radioelements' inter-relationships could clarify the geochemistry of uranium and thorium.…”
Section: Radioelement Distributionmentioning
confidence: 80%
“…Radioactive equilibrium in the study area can be estimated by the equilibrium factor (P), which was suggested by Reference [45] and applied by [41][42][43]46]. If the P-factor is ≥1, uranium is being added or removed.…”
Section: Radioactive Equilibriummentioning
confidence: 99%
“…The high HREEs content relative LREEs may clarify that LREEs could be precipitated with uranium elsewhere in the sheared granites. El Feky (2011) shows the presence of mirroring between HREEs and LREEs in Gattar granites and Hammamat sediments. Masuda et al (1987) classified the tetrad effect into two different types, M-and W-type (M-type in solid sample as residues and W-type in the interacting fluids as extract).…”
Section: Zr/hfmentioning
confidence: 96%
“…The accessory minerals are zircon, monazite, xenotime, fluorite, apatite, allanite and sphene. Magnetite, ilmenite, pyrite, chalcopyrite and pyrrohtite are the opaque minerals [16,21]. Uraninite, uranophane and geothite are the associated secondary minerals.…”
Section: Geological Setting Of the Northern Part Of The Study Area (Nmentioning
confidence: 99%